Cuba and Poland: an Outline of Comparative Analysis of Totalitarian Regimes - Bäcker, Roman (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2022)
The aim of the article is to find the similarities and differences between Poland and Cuba by comparing them totalitarian regimes. The research problem consisting in determining the importance of exogenous and endogenous factors favoring the regime or disintegrate it. In this case, the method of desk research is appropriate. The comparison was made using the same and operationalized criteria (hegemony or domination of the party-state apparatus, the intensity of political gnosis, and the scope and extent political mobilization) based on Juan Linz’s modified concept of totalitarianism. At the beginning of the 1960s, in Cuba, the uncivil society had a hegemonic position. In the 21st century, its status changed from hegemonic to dominant, closely linked with the totalitarian party-state apparatus. The political regime slowly evolved from strong to weak totalitarianism. In post-war Poland, the political regime evolved from strong to weak totalitarianism, to become authoritarian after 1980 behind the façade of an inoperable party-state apparatus, and in 1989 it collapsed. In both cases, exogenous factors were of much less importance than endogenous ones.

Celem artykułu jest poprzez porównanie reżimów totalitarnych Polski i Kuby znalezienie podobieństw i różnic między tymi dwoma państwami. Dzięki temu możliwe jest rozwiązanie problemu badawczego polegającego na określeniu znaczenia egzogennych i endogennych czynników sprzyjających tworzeniu i rozpadowi tego typu reżimów. Zastosowano w tym przypadku metodę analizy źródeł zastanych. Porównanie zostało dokonane przy pomocy jednolitych i zoperacjonalizowanych kryteriów (hegemonia lub dominacja aparatu partyjno-państwowego, intensywność gnozy politycznej oraz zasięg i zakres mobilizacji politycznej) opartych na zmodyfikowanej koncepcji totalitaryzmu Juana Linza. Na początku lat 60-tych XX wieku społeczeństwo nieobywatelskie i tym samym aparat partyjno-państwowy na Kubie miały pozycję hegemoniczną. W XXI wieku jest to dominacja. Kubański reżim polityczny powoli ewoluował od silnego do słabego totalitaryzmu. W powojennej Polsce reżim polityczny ewoluował od silnego do słabego totalitaryzmu, po 1980 r. stał się autorytarny za fasadą niesprawnego aparatu partyjno-państwowego, a w 1989 r. upadł. W obu przypadkach czynniki egzogenne miały o wiele mniejsze znaczenie niż endogenne.
Kuba i Polska. Zarys analizy porównawczej reżimów totalitarnych
Keywords: totalitarianism; political regime; Cuba; Poland; totalitaryzm; reżim polityczny; Kuba; Polska